SISTEM INFORMASI PEKAN ORIENTASI MAHASISWA BARU (POSMARU) UNHASY DENGAN MENGGUNAKAN ALGORITMA BRUTE FORCE - BUDI RIYANTO, ROCHMAD; SETYO PERMADI, GINANJAR; FATKUR RIZAL, MUHAMMAD (Inovate, 2023)
Developments in this era of computer technology with the power of a website allow us to develop amanagement information system using a computer. Therefore, a web-based new student orientationregistration information system is needed to facilitate and reduce processing time efficiency whenregistering new student orientation and handling registrant data managed by the committee and financefor new student admissions case studies at Hasyim Asy'ari University. The uses of making an InformationSystem include making it easier for students to register themselves in a computerized manner, facilitatingthe administration of receiving new student study orientations to manage registration data and saving itautomatically into the information system. In this study, the brute force method was used. This charactermatching is part of the brute force method and moves the pattern one by one and matches it with the text,so that it becomes the same pattern. This research resulted in a character matching test using the bruteforce method and a case study using a string matching search engine based on PHP programming.Hypertext Preprocessor (PHP) is the programming used and the database uses My Structure QueryLanguage (MySQL). New Student Study Orientation Registration Information System Created on a web-based basis, it is hoped that it can help the new student study orientation registration process become moreeffective and more efficient. And also the level of accuracy of the algorithm in this case study is 100% with a total data of 785 students. If the input data is in the database, if it is not registered, this data will notappear.Keywords: Information System, Brute Force Algorithm, PHP and MySQL.